Assessment of the Effect of Co-Digestion of Chicken Dropping and Cow Dung on Biogas Generation (Global Journal of Science Frontier Research, 2012)
Biogas production from 5 batch digesters containing varying ratios of mixture of chicken droppings and cow dung was studied for a period of 30 days at ambient temperature. Results from this study show that co-digestion of chicken droppings and cow dung increased biogas yield as compared to pure samples of either chicken droppings or cow dung. The maximum biogas yield was attained with mixtures in the proportions of 1:4. Several regression models were used to adequately describe the cumulative biogas production from these digesters. The polynomial correlation with R2 = 0.98 seemed to be more reliable in predicting gas production in anaerobic digestion of animal wastes. This tool is useful in optimizing biogas production from energy materials, and requires further validation and refinement. Hopefully, this study advances this increasingly growing area of animal wastes research.
Keywords: cow dung; chicken droppings; anaerobic; regression; biogas